PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN DAN KEPERCAYAAN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN - Aep Nurbani; Heru Mulyanto; Mursida Kusuma Wardani; Meli Andriyani (Jurnal Manajemen Kewirausahaan, 2019)
Marketing mix and customer satisfaction are two of the factors that are thought to be relatively large in influencing trust and have a large impact on loyalty. To prove the effect of each variable, this research was conducted with the aim to determine the effect of marketing mix, satisfaction and trust and its impact on loyalty. This research was conducted at Harvest City Housing by taking a sample of 100 consumers as research samples. The research used in this study is a causal type explanatory research that seeks to test the influence of variables in a structural model. The study was conducted by testing one exogenous variable and three endogenous variables. The research resulted in the findings of the model analysis results are feasible due to the influence of marketing mix, satisfaction and trust and their impact on consumer loyalty in the equation model 0.805 MM + 1-0.83 R2 = 0.17, 0.440 MM + 0.364 SC + error 0.89 R2 0.11 and 0.137 MM + 0.223 SC + 0.519 TR + error 0.82 R2 0.18 where: 1) The marketing mix affects satisfaction. 2) Marketing mix influences trust. 3). The marketing mix has no effect on loyalty. 4). Satisfaction does not affect Trust 5) Satisfaction does not affect loyalty. 6). Trust influences loyalty. Based on these findings, it is suggested to improve loyalty to improve the quality of the marketing mix, customer satisfaction and trust. Keywords : Marketing Mix, Satisfaction, Trust and Loyalty.